KEBIJAKAN TERHADAP PENGATURAN TINDAK PIDANA PERDAGANGAN ORGAN TUBUH MANUSIA DI INDONESIA - Masdiana Simbolon; Mukhlis R; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Trading human organs is a criminal offense regulated in Law Number 36 of 2009concerning Health. However, in this law there is no article that formulates aspects of organtrafficking and there is no confirmation that organ trafficking itself can be punished. And thereis no difference in sanctions between people who sell their own organs and people who sellother people's organs. The aim of writing this thesis is, firstly, to find out the regulation ofcriminal sanctions for the criminal act of trafficking in human organs in Indonesia. Second, tofind out the policy for regulating the criminal act of trafficking in human organs in criminallaw in IndonesiaThis research is classified as normative legal research or can also be called doctrinallegal research. Thus, this research uses secondary data sources consisting of primary,secondary and tertiary legal materials. In this research, the data analysis carried out isqualitative analysis and draws conclusions deductively.From the results of the research and discussion it can be concluded that, first, in theregulation of the criminal act of trafficking in human organs contained inLaw Number 36 of 2009 Article 64 paragraph (3), it has not explicitly mentioned theaspects of trafficking in human organs and there are no differences in sanctions in Article 192of the law. Second, there needs to be policy efforts or reform of criminal law, namelyemphasizing aspects of human organ trafficking considering that there are many ways to carryout this criminal act. As well as differentiating sanctions between people who sell their ownorgans and people who sell other people's organs as stated in the regulations of other countriessuch as Singapore and South Korea.Keywords: Policy-Regulation-Trafficking of Human Organs